KAJIAN PENGOBATAN TRADISIONAL CACAR MENURUT TERJEMAHAN LONTAR USADA KACACAR - Sutrisna, I Nyoman Gede Tri; Widyastuti, Ni Luh Gede; Cahyadi, Kadek Duwi (Jurnal Riset Kefarmasian Indonesia, 2019)
The Traditional medicine in Bali is a concept of Balinese culture that is used for generations. Usada is a knowledge of traditional Balinese medicine as a source of concepts to solve problems in the health sector. Healing (usada) is found in lontar called lontar usada. Lontar Usada Kacacar is one of the usada which discusses smallpox. The purpose of this study is to find out information contained in Lontar Usada Kacacar. Information includes the type of smallpox, treatment ingredients, dosage form and method of use. In addition, in research can be inform a plants that are used as traditional smallpox drugs. Healing in Bali is based on lontar, the research this time was carried out on eaves of Usada Kacacar. This research was conducted descriptively to the translation of Lontar Usada Kacacar translated by I Gusti Ngurah Wiriawan, S.S. The results of the translation of Lontar Usada Kacacar made in table form include the types of smallpox, medicinal herbs, how to use and use spells. The results of the table found information on 100 medicinal herbs, 75 types of smallpox, 107 types of plants, 10 types of methods of use and 16 methods of treatment accompanied by spells.